SULUT360 : APLIKASI INFORMASI MOBILE UNTUK DESTINASI PARIWISATA SULAWESI UTARA - Andria Wahyudi; Reymon Rotikan; Marchel Thimoty Tombeng; Falenrio Yehezkhiel Kalumata; Mercy Pricilia Debora Marentek (STMIK KAPUTAMA, 2021)
Tourism is an activity that is liked by almost everyone, tourism means that we carry out activities to visit tourist attractions that aim for recreation, vacation, or to unwind from the activities we usually do everyday. The provincial government of North Sulawesi must also follow its development by using a digital system available to make the government system better. There is also a system that uses 360-degree technology, namely virtual tours, virtual tours to simulate a place or location consisting of a series of The images from these images are combined to produce a 360 degree panoramic image, this method can take advantage of images or videos. For this reason, he wants to take advantage of this technology in the field of tourism in North Sulawesi so that tourist attractions can be known by local and foreign tourists and also for the government to be able to develop these tourist attractions. As for the problems that exist in North Sulawesi Province, namely the lack of technology or an Android-based application that provides complete information and information on tour packages in the area